Kontribusi Badan Komunikasi Pemuda Remaja Masjid Indonesia (BKPRMI) dalam Penguatan Kompetensi Pemuda Remaja Masjid di Kota Parepare - Gaffar, Arham (Institut Agama Islam Negeri Parepare, 2025)
This study analyzes the role of BKPRMI Parepare City as a forum for unifying the ukhuwah of mosque youth and youth who maximize the function of mosques not only for worship, but also as a space for character development and capacity to face contemporary challenges. Based on the Role Theory and Da'wah field theory, this qualitative study relies on documentation as the main source, with analysis stages in the form of word redaction, data presentation, and systematic conclusion drawn. The results show that BKPRMI carries out a coordinating, educational, and empowerment role effectively, reflected in a significant increase in the number of Mosque Youth (PRM) formed and strengthening its quality. Quality improvement is realized through a structured cadre agenda, thematic training (organization, leadership, digital-religious literacy), and a space for continuous actualization at the mosque and city levels. The findings affirm BKPRMI's contribution to strengthening the capacity, character, and socio-religious network of youth, while maintaining the integrity of ukhuwah in Parepare. Recommendations include standardization of the regeneration curriculum, monitoring-evaluation based on performance indicators, and cross-stakeholder collaboration